Does exogenous coenzyme Q10 affect aerobic capacity in endurance athletes? - Weston, S. B.; Zhou, S.; Weatherby, R. P.; Robson, S. J. (International Journal of Sport Nutrition and Exercise Metabolism, 1997)
The effect of orally supplemented coenzyme Q10 (CoQ10) on plasma CoQ10 concentration and aerobic capacity in endurance athletes was evaluated. Eighteen volunteer male road cyclists and triathletes, 8 in a CoQ10 supplementation group (QG) and 10 in a placebo group (PG), successfully completed the experimental protocol. Subjects were evaluated during and following graded cycling exercise tests, which were performed before and after 28 days of supplementation with 1 mg.kg-1.day-1 of CoQ10 or placebo. The presupplementation plasma CoQ10 concentration was significantly increased from 0.91 +/- 0.13 microgram.ml-1 to 1.97 +/- 0.27 microgram.ml-1 in QG following supplementation (p < .05). However, the CoQ10 supplementation regime had no consistently significant effect on oxygen uptake, anaerobic and respiratory compensation thresholds, blood lactate, glucose and triglyceride kinetics, heart rate, and blood pressure during and after graded cycling to exhaustion.